Evaluation of build food environments mapping approaches for policy decision making; perspective from Kenya, Benin, Uganda and Côte d’Ivoire - Akingbemisilu, Tosin; Jordan, Irmgard; Termote, Celine (2024)
Mapping the build food environment is important for understanding food availability, accessibility, and its impact on public health for policy and intervention planning. The Alliance of Bioversity and CIAT conducted food environment mapping, using three different mapping approaches; administrative, community, and centered approach.